2001
DOI: 10.1111/j.1151-2916.2001.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Additive on the Anatase‐to‐Rutile Phase Transition

Abstract: The effect of SiO 2 addition on the anatase-to-rutile phase transition was investigated by DTA, XRD, FTIR, and XPS. TiO 2 xerogels containing SiO 2 up to 20 mol% were prepared by mixing and hydrolyzing titanium tetraisopropoxide (TTIP) and tetraethylorthosilicate (TEOS) with HNO 3 as a catalyst. With increased amounts of SiO 2 in the xerogels, the following results were obtained: (1) the crystallization temperature of anatase increased from 415°C in pure TiO 2 to 609°C in 20-mol%-SiO 2 -containing xerogel in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
168
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(190 citation statements)
references
References 22 publications
(28 reference statements)
18
168
1
3
Order By: Relevance
“…Conversely, Yang and Ferreira [175] have suggested that the observed contraction in lattice parameters upon SiO 2 and/or Al 2 O 3 doping is evidence of solid solubility. Another study of the effects of SiO 2 doping on the lattice parameter of anatase [82] also suggested that Si 4? enters substitutionally, thereby decreasing the lattice parameter of anatase (and forming interstitial Ti 4?…”
Section: Importance Of Doping Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, Yang and Ferreira [175] have suggested that the observed contraction in lattice parameters upon SiO 2 and/or Al 2 O 3 doping is evidence of solid solubility. Another study of the effects of SiO 2 doping on the lattice parameter of anatase [82] also suggested that Si 4? enters substitutionally, thereby decreasing the lattice parameter of anatase (and forming interstitial Ti 4?…”
Section: Importance Of Doping Methodsmentioning
confidence: 99%
“…It has been suggested that cations of small radii and low valence accelerate the transition to rutile owing to the increase in oxygen vacancies that result from the assumed substitution of Ti 4? ions with cations of lower valences [43,109,157,164,165]. Charge neutrality thus requires an increase in the level of oxygen vacancies and/or the formation of Ti interstitials of lower valence [82,172]. Conversely, when cations of valence higher than 4 are assumed to substitute for Ti ions on the anatase lattice, this gives rise to the annihilation of existing oxygen vacancies and the formation of Ti interstitials of the same or lower valence.…”
Section: Cationic Dopantsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the mechanism of A to R transformation, it seems that phase transformation is a nucleation and growth process [22,26]. Also it is stated that in the synthesis of TiO 2 by various methods, the initial crystalline TiO 2 phase formed is generally anatase [27,28]. From a structural perspective, this could be due to the greater ease of the short-range ordered TiO 6 octahedra in arranging into long-range ordered anatase structure owing to the less-constrained molecular construction of anatase relative to rutile [29].…”
Section: Methodsmentioning
confidence: 99%
“…These elements are reported to inhibit the formation of rutile through the restriction of the atomic rearrangement involved in the phase transformation. [23,[34][35][36][37] The use of lower firing temperatures for similar coatings may result in similar mixed phase coatings if anatase-to rutile transformation promoting dopants, such as V, Co and Ni , are added [38] . However the use of lower firing temperatures may impede the formation of good coating adhesion.…”
Section: Phase Compositionmentioning
confidence: 99%